Analysis of mechanical properties of transition segment of road and bridge based on high-strength foam concrete - Hongmei Cao (Fracture and Structural Integrity)
The settlement difference in the transition section of road and bridge may lead to traffic accidents, which has many negative effects. Back filling of foam concrete behind abutment is a good method of treatment. In this study, a kind of high-strength foam concrete was designed for back filling of transition section of road and bridge, and the mechanical properties of the transition section of road and bridge were analyzed. It was found that only a large number of micro cracks  grew in high-strength concrete under a large number of load cycles, and structural damage did not happen, indicating the high-strength foam concrete had high strength and long service life; the static base pressure was about 40 KPa, indicating a small burden on the structure. Under the vehicle load, the vertical displacement of the transition section of road and bridge with back filling of high-strength foam concrete behind abutment was about 0.7 m and the maximum vertical stress was about -40 KPa, which was significantly lower than that of the ordinary concrete, and the stability was favourable, indicating that the high-strength foam concrete had good vibration absorption effect. The analysis results verifies the value of the high-strength foam concrete as the backfill material of the transition section of road and bridge, providing some theoretical basis for its application and popularization.